Role of hazelnut skin supplementation on plasma antioxidant status and cytokine profile in growing lambs - Ciliberti, Maria Giovanna; Santillo, Antonella; Caroprese, Mariangela; della Malva, Antonella; Natalello, Antonio; Bertino, Antonino; Albenzio, Marzia; Sevi, Agostino (Frontiers in Veterinary Science, 2024)
In this study, the effect of hazelnut skin dietary supplementation on antioxidant status and cytokine profile was evaluated in growing lambs. A total of 22 male lambs at the age of 2 months, balanced for their initial live weight (15.33 ± SD 1.79 kg), were selected and allocated into two experimental groups: the control group (CON) receiving a maize-barley-based concentrated diet, and the hazelnut group (HS) receiving supplementation with hazelnut skin (150 g/kg on the dry matter) as a maize substitute for the concentrate diet. The experiment lasted for 56 days. Peripheral blood was collected at 7, 35, and 56 days of the experiment. The free radical scavenging activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, the total antioxidant capacity assay (TAC), the reactive oxygen species (ROS), and reactive nitrogen species (RNS) were determined in plasma. The secretion of IL-1β, IL-6, and IL-10 cytokines was also determined by ELISA. The DPPH was affected by the interaction between feeding strategy and time of sampling (p = 0.039) with a higher level of DPPH at 7 days in the HS group than the CON group. The time of sampling affected the levels of plasma TAC (p = 0.016), while the ROS/RNS levels showed a higher value in the HS group (p < 0.001), on average. The antioxidant/oxidant index, which combines the TAC and the ROS/RNS levels, was not affected by the inclusion of hazelnut skin in the diet (p = 0.394). The cytokine profile showed a lower IL-6 secretion at both 35 and 56 days than at 7 days, on average. Furthermore, the feeding treatment affected the IL-1β level, showing a lower level in the HS group than in the CON group on average. Lambs from the HS group had higher IL-10 plasma levels than the CON group at 7 days of the experiment. The present data highlight an antioxidant effect and a modulatory role in the cytokine profile of HS supplementation in growing lambs.